1998
DOI: 10.1093/jnci/90.21.1661
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Features of Initial Adenomas as Predictors for Metachronous Adenomas of the Rectum

Abstract: The risk of metachronous adenomas is closely related to the pathology of initial adenomas, thus allowing identification of a high-risk group of adenoma patients for close surveillance after their initial polypectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
4
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 16 publications
1
52
4
7
Order By: Relevance
“…However, a candidate risk factor for metachronous carcinoma was not identified among such demographic characteristics as patients' age, sex, multiplicity, histology, and site of initial polyps. Although the histological grade of dysplasia of colon adenoma has been reported as a useful biomarker for metachronous development [12,21], our results could not confirm the observation. A possible interpretation for this disagreement is that dysplasia of the initial polyp determined metachronous incidence rather than in the distal colon [21], while second tumors mainly developed in the proximal colon in our study and also in another study [15].…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…However, a candidate risk factor for metachronous carcinoma was not identified among such demographic characteristics as patients' age, sex, multiplicity, histology, and site of initial polyps. Although the histological grade of dysplasia of colon adenoma has been reported as a useful biomarker for metachronous development [12,21], our results could not confirm the observation. A possible interpretation for this disagreement is that dysplasia of the initial polyp determined metachronous incidence rather than in the distal colon [21], while second tumors mainly developed in the proximal colon in our study and also in another study [15].…”
Section: Discussioncontrasting
confidence: 89%
“…Although the histological grade of dysplasia of colon adenoma has been reported as a useful biomarker for metachronous development [12,21], our results could not confirm the observation. A possible interpretation for this disagreement is that dysplasia of the initial polyp determined metachronous incidence rather than in the distal colon [21], while second tumors mainly developed in the proximal colon in our study and also in another study [15]. Furthermore, the inclusion of molecular or genetic markers of initial polyps may help establishing risk factors for metachronous development of carcinoma (for a recent review, see [7]).…”
Section: Discussioncontrasting
confidence: 89%
“…Polyps less than 5 mm in diameter are poorly described in the literature, and the optimal approach for DP management remains controversial. There is convincing evidence that advanced histology, defined as the presence of a villous component and/or high-grade dysplasia, increases the risk of CRC [2,3,18,19]. It was previously reported that relatively high numbers of carcinomas originated from diminutive lesions.…”
Section: Discussionmentioning
confidence: 99%
“…(1) e YANG et al (21) mostraram, através de estudos com retossigmoidoscopias, que pólipos adenomatosos volumosos (maiores que 10 mm) apresentam associação positiva com o risco de neoplasia avançada durante a vigilância endoscópica.…”
Section: Discussionunclassified
“…As características dos adenomas ressecados consideradas como preditivas para lesões avançadas futuras são: três ou mais adenomas, tamanho maior que 10 mm, histologia vilosa e displasia de alto grau (1,8,16,19,21) . Atualmente sugerem-se para pacientes sem outros fatores de risco para câncer colorretal, exceto a presença de pólipos intestinais ressecados, as seguintes recomendações: (1) pacientes com pólipos hiperplásicos, especialmente retais, sejam considerados como tendo colonoscopia normal; (2) pacientes com até dois adenomas menores que 10 mm ou com displasia de baixo grau sejam reexaminados em 5 anos ou mais; (3) pacientes com três ou mais adenomas ou, pelo menos um deles maior de 10 mm ou com componente viloso ou displasia de alto grau, sejam submetidos a nova colonoscopia em 3 anos, desde que todos os pólipos tenham sido adequadamente removidos; (4) pacientes com mais de 10 pólipos devam repetir o exame num período inferior a 3 anos, de acordo com julgamento clínico, assim como devam ser considerados para possível síndrome familial subjacente, e (5) pacientes com pólipos sésseis removidos endoscopicamente por técnica de fatiamento devam fazer revisão colonoscópica em intervalos de 2 a 6 meses para verificar a remoção completa das lesões (19) .…”
Section: -Jul/set 2009unclassified